Economic crisis in developing countries : new perspectives on commodities, trade and finance - Hewitt, Adrian, ed (London : Pinter Publishers, 1993)
Economics
Keywords: Developing countries - Economic conditions; Prices - Developing countries; International economic relations; Trade; Finance